2017
DOI: 10.1128/aac.02352-16
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Sterol Biosynthetic Pathway of Pythium insidiosum and Related Oomycetes Contributes to Antifungal Drug Resistance

Abstract: Pythiosis is a life-threatening infectious disease caused by the oomycete Pythium insidiosum. Direct exposure to Py. insidiosum zoospores can initiate infections of the eye, limb, gastrointestinal tract, or skin/subcutaneous tissue. Treatments for pythiosis have mostly relied on surgery. Antifungal drugs are generally ineffective against Py. insidiosum. However, one patient with an invasive Py. insidiosum infection recovered completely following treatment with terbinafine and itraconazole. Additionally, the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 53 publications
(33 reference statements)
1
76
0
1
Order By: Relevance
“…This microorganism is unable to synthesize ergosterol because it has an incomplete set of sterol biosynthetic enzymes [2]. This is believed to be the reason behind antifungal treatment failure in pythiosis [1, 35].…”
Section: Introductionmentioning
confidence: 99%
“…This microorganism is unable to synthesize ergosterol because it has an incomplete set of sterol biosynthetic enzymes [2]. This is believed to be the reason behind antifungal treatment failure in pythiosis [1, 35].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro susceptibility assays. The growths of 27 P. insidiosum strains (Table 1), upon exposure to disulfiram, were measured using the agar-based (12,32) and broth-based (see below) susceptibility methods. The experiments were performed in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…An agar plug with the organism was placed on the SD agar or immersed in the SD broth containing various concentrations (i.e., 0, 2, 4, 8, 16, 32, 64, and 128 mg/liter) of disulfiram (purity, Ն98%; solvent, dimethyl sulfoxide [DMSO]; manufacturer, Unidrug Innovative Pharma Technologies, Ltd., India) and incubated at 37°C for 2 days. For the agar-based susceptibility method (12,32), two perpendicular diameters of a P. insidiosum colony were averaged, subtracted by the agar plug diameter (5 mm), and divided by half. The actual radial growth of a disulfiram-exposed strain was calculated to the "percent growth" in relation to that of the same strain without drug exposure (control).…”
Section: Methodsmentioning
confidence: 99%
“…Disease can occur in humans and animals (ie horses, cattle and dogs), and due to its aggressiveness, most cases are treated with extensive surgery to remove the affected organ . Antimicrobial treatment of pythiosis remains controversial once it does not respond appropriately to antifungal drugs, and this resistance was recently linked to the fact that P. insidiosum contains an incomplete set of sterol biosynthetic enzymes …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Antimicrobial treatment of pythiosis remains controversial once it does not respond appropriately to antifungal drugs, and this resistance was recently linked to the fact that P. insidiosum contains an incomplete set of sterol biosynthetic enzymes. 3 Studies on pythiosis have been conducted using rabbits as an experimental model since Witkamp 4 intraperitoneally or intravenously injected hyphae and successfully reproduced pythiosis in rabbits. This model was updated by Miller and Campbell 5 when they implicated the zoospores as the infecting units and demonstrated that immunosuppression is unnecessary for the infection to develop in rabbits.…”
Section: Introductionmentioning
confidence: 99%